2022
DOI: 10.3390/healthcare10101974
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Social Determinants to Educational Outcomes: Geospatial Considerations

Abstract: In recovering from one of the worst educational crises in recorded history due to the pandemic, in a mission to rebuild and become more resilient, there has been a heightened urgency to provide resources to communities most in need. However, precisely identifying those needs have become all the more important due to the increase in popularity of e-learning as a suitable option and the improvement of technologies. Most notably, socially disadvantaged and historically marginalized communities were disproportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Yet, as the nation becomes more diverse (see Table 2), it continues to remain racially segregated (United States Government Accountability Office, 2022) not only in terms of where people live (see Figure 3), but also in terms of economic and social mobility (Chetty et al, 2018; Opportunity Insights, n.d.). Figure 3 is a web-based, interactive map, accessible through this link, and shows an uneven geographic distribution of ethnic and systemically marginalized groups (Banerjee et al, 2022). The need to create health equity is urgent.…”
Section: Interprofessional Faculty and Program Developmentmentioning
confidence: 99%
“…Yet, as the nation becomes more diverse (see Table 2), it continues to remain racially segregated (United States Government Accountability Office, 2022) not only in terms of where people live (see Figure 3), but also in terms of economic and social mobility (Chetty et al, 2018; Opportunity Insights, n.d.). Figure 3 is a web-based, interactive map, accessible through this link, and shows an uneven geographic distribution of ethnic and systemically marginalized groups (Banerjee et al, 2022). The need to create health equity is urgent.…”
Section: Interprofessional Faculty and Program Developmentmentioning
confidence: 99%
“…For instance, the safety level of educational facilities has a direct correlation with the investment in education resources (Wang et al, 2022). Moreover, the impacts of learners' experience as influenced by educational resources on their lives are extensive and long term, and some studies have even found that there is a relationship with health (Banerjee et al, 2022). The attention of city planners and policymakers alike should be on those goals that come under the banner of social sustainability, such as educational resource equity, especially when designing new human settlements or retrofitting existing ones (Sodiq et al, 2019).…”
Section: Urban-rural Differences In Primary School Resourcesmentioning
confidence: 99%